Seasonal Behavior of Pharmaceuticals and Personal Care Products Within Chilean Rural Wwtps Under Covid-19 Pandemic Conditions - Toledo-Neira, C; Toledo-Neira, C; Villamar-Ayala, C; Plaza-Garrido, A (Elsevier Ltd, 2023)
During the COVID-19 pandemic, the consumption of pharmaceuticals and personal care products (PPCPs) increased exponentially. There is an associated risk concerning the presence of PPCPs from wastewater, mainly in rural zones of emerging countries, where sanitation tends to be poor or inefficient. Therefore, this study aimed to evaluate the seasonal behavior of PPCPs within Chilean rural wastewater treatment plants (WWTPs) under COVID-19 pandemic conditions. Ten Chilean rural WWTPs were monitored during 2021, both in the cold (May–September) and warm (November – December) months, being collected semi-composite samples (influent/effluent). WWTPs were based on activated sludge, aerobic lagoons, rotatory discs, activated sludge + bio discs, constructed wetlands, and vermifilter. Physicochemical parameters and PPCPs (azithromycin, ciprofloxacin, caffeine, ibuprofen, losartan, and triclosan) compounds were monitored. Results showed that PPCPs, such as antibiotics (azithromycin, ciprofloxacin: 14.7 – 100%), stimulants (caffeine: 41.5 – 100%), NSAIDs (ibuprofen: 32.9–100%), β-blockers (losartan: 43.5–100%), and disinfectants (triclosan: 45.9–100%) were variably removed. Non-significant differences (p > 0.05) of the PPPCs (effluent concentrations/efficiencies) were reported regarding seasonality and treatment typologies. Moreover, azithromycin, ciprofloxacin and triclosan reported positive correlations (Ɵ ≈ 0 °) with solids. Finally, this study evidenced that COVID-19 pandemic conditioned seasonally variability of PPCPs from wastewater. © 2023 Elsevier Ltd
Keywords: Wastewater; COVID-19; Seasonality; Nitrite; Azithromycin